2008
DOI: 10.1177/0961203308090990
|View full text |Cite
|
Sign up to set email alerts
|

Haemolytic anaemia in a multi-ethnic cohort of lupus patients: a clinical and serological perspective

Abstract: Systemic lupus erythematosus is a chronic autoimmune disease that can be associated with a variety of haematological manifestations. We identified 76 patients with haemolytic anaemia in a cohort of 1251 unrelated female lupus patients enrolled in our studies. The presence of the various American College of Rheumatology clinical criteria for lupus and serological specificities were determined in lupus patients with haemolytic anaemia and compared with a group of race-matched control lupus patients without haemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 13 publications
4
39
0
2
Order By: Relevance
“…Mean age of wAIHA onset was 51.7 ± 20.5 years in primary wAIHA group and 54.3 ± 25.7 years in secondary wAIHA, which is statistically not significant. Regarding clinical symptoms at the time of onset, 93.10% (27) in primary wAIHA group and 67.39% (31) in secondary wAIHA group reported it.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean age of wAIHA onset was 51.7 ± 20.5 years in primary wAIHA group and 54.3 ± 25.7 years in secondary wAIHA, which is statistically not significant. Regarding clinical symptoms at the time of onset, 93.10% (27) in primary wAIHA group and 67.39% (31) in secondary wAIHA group reported it.…”
Section: Resultsmentioning
confidence: 99%
“…Diagnosis may be difficult in some patients with IgM warm antibodies, cold antibodies with low titers, DAT negativity, or Donath-Landsteiner antibodies. The type of antibodies and diseases underlying are represented in Table 1 [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Sudulagunta Et Al J Hematol 2017;6(1):12-20mentioning
confidence: 99%
“…[1][2][3] Although not among the most common lupus manifestations, serositis is still frequent, seen in 12%-45%. [4][5][6][7][8][9][10] The frequency of pericarditis ranges from 10% to 24%, and of pleurisy ranges from 15% to 34%, [10][11][12][13][14][15] suggesting that these two types of serositis have similar frequencies. In one study, 24% of patients with SLE with serositis had relapsed during the follow-up period.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] The results from a few past studies have shown some potential associations of pleurisy or pericarditis in SLE, as summarised in table 1. [11][12][13][14][15] Feng et al found that male gender was associated with both serositis (p<0.05) and pleurisy (p<0.05). 11 In only one study, haemolytic anaemia was associated with pericarditis (p=0.0019) and pleurisy (p=0.028).…”
Section: Introductionmentioning
confidence: 99%
“…37 Imatinib, a specific PDGF receptor-targeting tyrosine kinase inhibitor initially developed to treat chronic myeloid leukemia, has been shown to significantly improve survival and delay the onset of proteinuria in lupus-prone mice. 38 …”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%